Pandora's Millions - Smith, George O. (George Oliver), 1911-1981; Orban, Paul, 1896-1974 (Salt Lake City, UT : Project Gutenberg, 2022)
"Pandora's Millions" by George O. Smith is a science fiction novel likely written in the mid-20th century. The narrative explores a future society grappling with the consequences of a technological breakthrough that allows for the duplication of physical items, fundamentally altering economic principles. It examines themes of abundance, value, and societal structures in a world where the lines between want and necessity blur. The story primarily follows Keg Johnson, the chief executive of Interplanet Transport, and Don Channing, a scientist who has developed a matter transmitter that enables the duplication of objects. As the technology threatens traditional economic systems by making everything readily available, both men struggle to adapt to a new reality. Keg seeks to establish a new means of trade based on unique services rather than material wealth, while others, like lawyer Mark Kingman, aim to exploit the current chaos for personal gain. The plot unfolds as characters navigate societal upheaval, the devaluation of money, and the search for a medium of exchange that could give stability to their world. Ultimately, the narrative reflects on the implications of technology on human relationships, societal roles, and the nature of value itself. (This is an automatically generated summary.)
Release date is 2022-05-06
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Inventions -- Fiction; Space stations -- Fiction; Technology -- Fiction